Mental health of Australian Aboriginal women during pregnancy: identifying the gaps - Prandl, Kelly; Rooney, Rosanna; Bishop, Brian (Springer-Verlag Wien, 2012)
Despite Australia’s high standard of health care provision, Australian Aboriginal women continue to experience poor pregnancy outcomes in terms of maternal and foetal morbidity and mortality. In an attempt to improve these outcomes, health care providers have developed targeted antenatal programmes that aim to address identified health behaviours that are known to contribute to poor health during pregnancy. While some areas of improvement have been noted in rates of engagement with health services, the rates of premature births and low birth weight babies continue to be significantly higher than in the non-Aboriginal population. It appears that Australian researchers have been focused on the behaviour of the individual and have failed to fully consider the impact that social and emotional well-being has on both health behaviours and pregnancy outcomes. This review has highlighted the need for an approach to both research and clinical practice that acknowledges the Aboriginal view of health which encompasses mental, physical, cultural and spiritual health. Until clinicians and Aboriginal women have a shared understanding of how social and emotional well-being is experienced by Aboriginal women, in other words their explanatory model, it is unlikely that any meaningful improvements will be seen.